Determination of whole blood and plasma viscosity in term neonates by flow curve analysis with the LS300 viscometer 1 - Kuß, Navina; Bauknecht, Elisa; Schmidt, Claudia; Gehm, J.; Gehm, L.; Pöschl, Johannes; Ruef, Peter (Clinical hemorheology and microcirculation, 2016)
Determination of shear stresses at given shear rates allow approximation of flow curves by mathematical models and to calculate viscosities of non-Newtonian fluids. In term neonates, the mean arterial blood pressure (MAP) is markedly below that of adults, therefore rheological properties of blood play an important role in maintaining perfusion.